Evaluation of Antioxidant, Cytotoxic, and Antibacterial Activities of Dactyloctenium australe Steud. (Bangladesh Pharmaceutical Journal, 2025)
The widespread use of traditional medicine and medicinal plants as a normative basis for maintaining good health has been observed in the majority of developing countries. An in vitro antioxidant study of Dactyloctenium australe showed statistically significant (p < 0.01) antioxidant activity by scavenging free radicals, compared to the standard ascorbic acid. The IC50 value for the chloroform soluble fraction (CHS) was 14.16 ± 0.11 μg/ml, followed by the carbon tetrachloride soluble fraction (CTS) with IC50 values of 18.10 ± 1.09 μg/ml and 24.54 ± 1.34 μg/ml. The CHS fraction also demonstrated the highest cytotoxic activity in vitro, with an LC50 value of 15.14 μg/ml, compared to the standard vincristine sulfate (0.451 μg/ml). Furthermore, for antibacterial activity, the methanolic extract and its CHS fraction exhibited distinct zones of inhibition against Gram-positive bacteria, while the petroleum ether soluble fraction (PS) and CTS fraction also showed significant activity. Dactyloctenium australe exhibited notable antibacterial activity against Staphylococcus aureus (a Gram-positive bacterium) and Salmonella paratyphi, Salmonella typhi and Vibrio cholerae (Gram-negative bacteria), compared to the standard antibiotic ciprofloxacin.Bangladesh Pharmaceutical Journal 28(2): 160-163, 2025 (July)